Algorithm of complex therapy and prevention of emotional burnout in doctors-psychiatrists during the war and its effectiveness - Levin, Taras (Journal of Education, Health and Sport, 2024)
Abstract. The purpose - to develop and determine the effectiveness of the algorithm of complex therapy and prevention of emotional burnout (EB) among psychiatrists during the war, to resolve the issue of its recommendation for wide implementation in the system of mental health care institutions. The research sample, which was formed in compliance with the principles of biomedical ethics and based on informed consent, included 120 psychiatrists who worked in the city of Kyiv in the period from February 24, 2022. During 2022, the persons under examination were divided into three groups: the first group included 37 persons (30.8%) – doctors with no signs of professional maladjustment (PMA), and a low level of EB; the second group consisted of 57 persons (47.5% ) with signs of professional PMA, and a moderate level of EB; the third group consisted of 26 persons ( 21.7%) and they were respondents with clinically established and pronounced PMA, and a high level of EB. As a result of the study, the personal, psychopathological, psychosocial, professional and emotional-interpersonal factors of the formation and progression of EB among psychiatrists during the war were established, and their interrelationships in its genesis, on the basis of which the basic principles of a comprehensive approach to the therapy and prevention of EB were formulated for psychiatrists (complexity, personalization, phasing and availability), the main goals of treatment and prevention measures are defined and 4 therapeutic strategies of diagnosis, therapy and prevention are proposed within the framework of providing specialized medical care to psychiatrists during the war. These are recommended to be implemented taking into account the degree PMA as a key descriptor of EB, and in accordance with the key vectors of pathological changes in the respondents. The implementation and further evaluation of the effectiveness of the mentioned measures proved their effectiveness in eliminating manifestations of EB and PMA, normalization of mental state with levelling of psychopathological symptoms, improvement of social and psychological adaptation and quality of life of psychiatrists. The results obtained make it possible to recommend this algorithm for wide implementation in the practice of mental health care institutions.